PENGARUH GARAM NaCl TERHADAP KINERJA PROSES BIOLOGIS ANAEROBIK - Mahmud, Ikbal (Center for Environmental Technology, 2005)
Anaerobic treatment of synthetic wastewater with a high NaCl content was investigated for its effect on the process. The synthetic wastewater, including NaCl up to 40 g/l, was treated anaerobically by draw-and-fill method at a treatment temperature of 37Ã¢â€žÆ’ and volumetric loading of rate TOC of 1 g/l/d. TOC removal efficiency and rate of gas evolution rate gradually decreased as salt content increased, although stable operation was maintained. TOC removal efficiency remained high at concentration of NaCl up to 20 g/l, although it fell to 82 % at 30 g NaCl/l. The gas yield at 10, 20 and 30 g NaCl/l were 1.35; 1.10 and 1.00 l/g-TOC loaded, which corresponded to 96; 83 and 78% of that without NaCl, respectively. The content of methane in the evolved gas was 50 to 55% throughout the experiment. Stable operation could not be maintained at 40 g NaCl/l since the TOC removal efficiency gradually decreased with the rapid increased in levels of volatile fatty acidsKata kunci : fermentasi metana, garam NaCl, konduktifitas, asam-asam organik, biogasÃ‚Â